Strengthening Local Economy Resilience: Business Model Innovation based on Digital for Date Palm Agribusiness in Ayuthayya Thailand - Sri Retnaning Sampurnaningsih; Rachmawaty Rachmawaty; Umi Rosilawati; Bandit Aroman (Indonesian Journal of Society Engagement, 2025)
The local economy in Ayutthaya, Thailand, demonstrates considerable potential in the agribusiness sector, particularly date palm cultivation, which possesses both domestic and international market value. However, micro, small, and medium enterprises (MSMEs) in this sector face constraints related to digital marketing capability, business model innovation, and access to broader markets. Digital transformation offers a strategic solution through technology-based business model innovation integrating online promotion, e-commerce platforms, digital payment systems, and product branding.This community service program aimed to: (1) identify the potential and challenges of the local date palm agribusiness; (2) develop an innovative digital-based business model adapted to local conditions; and (3) provide training and mentoring for business owners. The implementation methods consisted of field surveys, business model formulation using the Business Model Canvas framework, digital marketing training, and implementation assistance. The program outcomes indicate increased awareness and adoption of digital promotion tools, particularly WhatsApp Business and Instagram, improved understanding of structured business strategy through the Business Model Canvas, and the preparation of scientific publications. The intervention is expected to strengthen local economic resilience and expand market opportunities for date palm MSMEs in Ayutthaya through sustainable digital adoption. Abstrak Perekonomian lokal di Ayuthayya, Thailand, memiliki potensi besar di sektor agribisnis, khususnya budidaya kurma (date palm) yang memiliki nilai pasar tinggi, baik domestik maupun internasional. Namun, pelaku usaha menghadapi tantangan dalam pemasaran digital, inovasi model bisnis, dan akses pasar global. Transformasi digital dapat menjadi solusi strategis melalui inovasi model bisnis berbasis teknologi yang mengintegrasikan pemasaran online, e-commerce, pembayaran digital, dan branding produk. Kegiatan PkM ini bertujuan untuk (1) mengidentifikasi potensi dan tantangan agribisnis kurma di Ayuthayya, (2) merancang inovasi model bisnis berbasis digital yang sesuai dengan kondisi lokal, dan (3) memberikan pelatihan serta pendampingan kepada pelaku usaha. Metode pelaksanaan mencakup survei lapangan, perancangan model bisnis menggunakan Business Model Canvas, pelatihan pemasaran digital, dan pendampingan implementasi. Luaran yang dihasilkan adalah kesadaran akan pentingnya promosi digital berupa WA business dan  IG umkm kurma Ayuthayya, model bisnis BMC dan artikel ilmiah. Diharapkan program ini dapat meningkatkan ketahanan ekonomi lokal dan memperluas peluang pasar bagi pelaku usaha kurma di Ayuthayya. Kata Kunci: ekonomi lokal; BMC; digitalisasi; agribisnis kurma; UMKM